Comparative Insights into Acute Gastroenteritis in Cattle Caused by Bovine Rotavirus A and Bovine Coronavirus - Vjekoslava Kostanić; Valentina Kunić; Marina Prišlin Šimac; Marica Lolić; Tomislav Sukalić; Dragan Brnić (Veterinary Sciences)
Acute gastroenteritis (AGE) in cattle significantly impacts the economy due to relatively high morbidity and mortality and decreased production. Its multifactorial nature drives its global persistence, involving enteric viruses, bacteria, protozoa, and environmental factors. Bovine Rotavirus A (BoRVA) and bovine coronavirus (BCoV) are among the most important enteric RNA viruses causing AGE in cattle. These viruses infect intestinal enterocytes, leading to cell damage and consequently to malabsorption and diarrhea. BoRVA primarily affects calves under 14 days old with gastrointestinal clinical signs, while BCoV affects all ages, causing gastrointestinal and respiratory distress. The economic impact of BoRVA and BCoV, along with their interspecies transmission potential, warrants attention. This concise review discusses the molecular structure, epidemiology, pathogenesis, clinical signs, diagnosis, treatment, and preventive measures of BoRVA and BCoV while providing a comparative analysis. By offering practical guidance on managing such viral infections in cattle, these comparative insights may prove valuable for veterinarians in clinical practice.